Nineteenth century biological conditions on the high central plains - Scott A. Carson (Center for Economic Studies and ifo Institute (CESifo), 2012)
Little work has been done on the biological conditions for the US Central Plains. Throughout the late 19th and early 20th centuries, black and white statures in Nebraska increased with economic development, indicating that biological conditions improved as Nebraska's output market and agricultural sectors embedded. Illustrating the importance of rural environments with stature growth, farm laborers were taller than common laborers. Urbanization and industrialization were significant in stature variation, and closer proximity to trade routes and waterways were inversely related with statures in Nebraska.
Keywords: J15; J70; I20; I31; N31; 330; agricultural development; black and white biological conditions